Resistance of the house fly , Musca domestica, to some synthetic organic insecticides in Fortaleza, Ceará - Bastos, José Alberto Magalhães (Pesquisa Agropecuaria Brasileira, 2014)
Tests were carried out under laboratory conditions to determine the LD50 of DDT, lindane, aldrin, dieldrin to the house fly, Musca domestica L., in Fortaleza, Ceará, Brazil. House flies were exposed to residues of DDT, lindane, aldrin and dieldrin on glass surfaces. To obtain LD50 the following number of micrograms of inseeticides were needed per 40 cm² of surface area: 117.5 DDT; 18.5 1indane 45 aldrin, and 43 dieldrin.